Immature Platelet Fraction (IPF) as a predictor of severity in patients with COVID-19: an integrative review (Research, Society and Development, 2022)
Objective: analyze the scientific evidence regarding the use of Immature Platelet Fraction (IPF) as a predictor of severity of COVID-19. Methods: This is an integrative literature review. The guiding question used was “IPF can be a parameter used as a prognosis of severity in patients with COVID-19?”. To answer this question, were selected studies Pubmed and in the Virtual Health Library (VHL). The search terms used were immature platelets, reticulated platelets, immature platelet fraction, COVID-19 and SARS-CoV-2. The terms were searched in portuguese and english, using the boolean operator “and”. Results: after applying the selection criteria, five articles were used. The studies reviewed found a significant increase in immature platelets in patients with severe COVID-19 compared to mild and moderate form of the disease. In addition, IPF proved to be differential biomarker between patients with COVID-19 and patients with cardiovascular risks. Conclusion: the need for further research was evidenced in order to accurately determine the IPF cohort values that can be used in the clinical management of patients with COVID-19.